(NpROIZWEDENIQ(B: [1887-1909] /s (N~ASTX (B2s - (NbUNIN(B, (NiWAN aLEKSEEWI^s ((NmOSKWA(B:s (NhUDOVESTWENNAQ LITERATURA(B,s, 1987)
(NwO (B2 (NTOM WO[LI RASSKAZY i(B. (Na(B. (NbUNINA (B1887 - 1909 (NGODOW (B("(NpEREWAL(B", "(NtANXKA(B", "(NsWQTYE gORY(B", "(NaNTONOWSKIE QBLOKI(B", "(NsANI(B" (NI DR(B. )s
rus
Keywords: (NpOWESTI I RASSKAZYs